Teachers' subject competence in digital times - Kroksmark, Tomas (Education Inquiry, 2015)
The study aims to generate new knowledge regarding how subject teachers in children's and young people's education conceive of the didactic relationship between their own subject knowledge and the computer's infinite possibilities concerning information and knowledge. The theoretic frames of the study lie within modern phenomenology with special inspiration from the concept of the life-world. This applies to both the relationship among subject knowledge, technology and human beings, and the theory of science and methodological instrumentation and analysis. The empirical turn of the life-world phenomenology makes it possible to collect data through research interviews. The study comprises 41 teachers in five different schools who have worked in One-to-One environments for varying lengths of time, between 24 and 36 months. The analysis of the interviews shows that the teachers perceive and distinguish 11 different qualities compiled in three main categories where they describe the didactic relationship between their own subject knowledge and the computer's infinite potential concerning information and knowledge.